Thematic Interpretation of Qur'an Deliberation as the Basis of Social Reconciliation - Ajuba, Taufik; Abubakar, Achmad; Mahfudz, Muhsin (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
The purpose of this research is to examine the concept of syūrā deliberation in the Qur'an as the foundation of social ethics and reconciliation in contemporary society, which faces a crisis of dialogue and religious polarization. The method used is the tafsīr maudhūʿī approach (thematic interpretation combined with contextual hermeneutic analysis). The focus of the study is directed to three main verses: QS Āli ʿImrān 3:159, QS Ash-Shūrā 42:38, and QS Al-Baqarah 2:233. In the analysis, the author integrates the views of the classical mufassir alṬabarī, Ibn Kathīr, al-Qurṭubī and the modern thinker M. Quraish Shihab, alṬabāṭabāʾī to interpret the deliberative value of the Qur'an in a broader socio-ethical context. The study's findings reveal that the value of syūrā encompasses three primary dimensions: recognition and acceptance of taʿāruf, diversity, tolerance of tasāmuh and mutual respect, and islāḥ (reconciliation and social restoration). These three dimensions form the conceptual framework of the "Qur'anic Ethics of Reconciliation," which has relevance to John Paul Lederach's transformative theory of reconciliation and Jürgen Habermas's concept of communicative action, but is enriched by a spiritual dimension derived from divine revelation. Conceptually, this study concludes that the Qur'an is not only a moral-theological guideline, but also an epistemological source for the development of modern Islamic social theories oriented towards peace, spirituality, and inclusivity.